Sixty Years of Global Inflation: A Post-GFC Update - Raphael Auer; Mathieu Pedemonte; Raphael Schoenle (CESifo GmbH, 2024)
Is inflation (still) a global phenomenon? We study the international co-movement of inflation based on a dynamic factor model and in a sample spanning up to 56 countries during the 1960-2023 period. Over the entire period, a first global factor explains approximately 58% of the variation in headline inflation across all countries and over 72% in OECD economies. The explanatory power of global inflation is equally high in a shorter sample spanning the time since 2000. Core inflation is also remarkably global, with 53% of its variation attributable to a first global factor. The explanatory power of a second global factor is lower, except for select emerging economies. Variables such as a broad dollar index, the US federal funds rate, and a measure of commodity prices positively correlate with the first global factor. This global factor is also correlated with US inflation during the 70s, 80s, the GFC, and COVID. However, it lags these variables during the post-COVID period. Country-level integration in global value chains accounts for a significant proportion of the share of both local headline and core inflation dynamics explained by global factors.
Keywords: E31; E52; E58; F02; F41; F42; F14; F62; 330; globalization; inflation; Phillips curve; monetary policy; global value chain; international inflation synchronization